Experimental analysis of cell pattern on grid fin aerodynamics in subsonic flow. (March 2020) - Tripathi, Manish; Sucheendran, Mahesh M; Misra, Ajay
Grid fins consisting of a lattice of high aspect ratio planar members encompassed by an outer frame are unconventional control surfaces used on numerous missiles and bombs due to their enhanced lifting characteristics at high angles of attack and across wider Mach number regimes. The current paper accomplishes and compares the effect of different grid fin patterns on subsonic flow aerodynamics of grid fins by virtue of the determination of their respective aerodynamic forces. Furthermore, this study deliberates the impact of gap variation on aerodynamics of different patterns. Results enunciate enhanced aerodynamic efficiency, and lift slope for web-fin cells and single diamond patterns compared to the baseline model. Moreover, the study indicates improved aerodynamic performance for diamond patterns with higher gaps by providing elevated maximum lift coefficient, delayed stall angle, and comparable drag at lower angles. The study established the presence of an additional effect termed as the inclination effect alongside the cascade effect leading to deviations with respect to lift, stall, and aerodynamic efficiency amongst different gap variants of the individual patterns. Thus, optimization based on the aerodynamic efficiency, stall angle requirements, and construction cost by optimum pattern and gap selection can be carried out through this analysis, which can lead to elevated aerodynamic performance for grid fins.